Assessing sexual practices and beliefs among university students in Khartoum, Sudan; a qualitative study - Husameddin Farouk Elshiekh; Hein de Vries; Ciska Hoving (Taylor & Francis Group, 2021)
University students in Sudan are more at risk of contracting HIV than the general population, due to a high rate of sexual activity and low uptake of preventive measures such as condoms. Hence, they are considered an important target for HIV prevention programmes. This study explored students` beliefs about abstinence and pre-marital sex. Thirty semi-structured individual interviews were conducted, based on constructs from the Integrated Change (I-Change) Model. The study sample included 16 (53%) male and 14 (47%) female university students. Their average age was 21.2 years (Range 18-27 and SD 2.5). Both sexual abstainers (N = 19) and sexually active students (N = 11) perceived HIV severity and susceptibility. Most of the participants had a positive attitude towards abstinence. However, sexually active students also perceived some advantages of engaging in sexual practices, such as sexual pleasure and proving adulthood. Sexually active students more often mentioned being influenced in their sexual practices by their peers than by their families. Sexually active students reported lower self-efficacy to refrain from sex than abstainers. Interventions that seek to promote abstinence among those willing to achieve this should stress the advantages of abstinence from sex until marriage, offer tools to resist peer pressure and enhance self-efficacy to abstain. These findings can be used to develop comprehensive HIV prevention programmes that primarily promote abstinence among university students who are not yet sexually active but also consider promoting condom use and other safer-sex practices among those who are sexually active. These interventions should also be gender-sensitive to address the needs of both male and female students.